2014
DOI: 10.1249/mss.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Adaptations Associated with Knee Joint Angle-Specific Force Change

Abstract: The EMG/Mmax, although not VA%, results suggest that neural adaptations underpinned training-related changes at short quadriceps lengths, but hypertrophic changes predominated after training at long lengths. The findings of this study should contribute to the development of more effective and evidence-based rehabilitation and strength training protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
193
7
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(217 citation statements)
references
References 45 publications
13
193
7
4
Order By: Relevance
“…In the 2000s, some studies showed an increase in fascicle length following resistance or competitive training [43][44][45][46][47][48][49][50][51][52][53] . Overall, training-induced increases in fascicle length are accompanied by an increase in muscle size (muscle hypertrophy, which is defined as an increase in muscle fiber area, muscle thickness, anatomical crosssectional area or volume in this article), although four studies failed to find muscle hypertrophy 45,52,54,55) and two studies did not show the data on muscle size 56,57) . Two studies observed a decrease in fascicle length of the gastrocnemius with 58) and without 59) muscle hypertrophy, and Timmins et al 55) showed a decrease in the fascicle length of BF without muscle hypertrophy.…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 81%
See 2 more Smart Citations
“…In the 2000s, some studies showed an increase in fascicle length following resistance or competitive training [43][44][45][46][47][48][49][50][51][52][53] . Overall, training-induced increases in fascicle length are accompanied by an increase in muscle size (muscle hypertrophy, which is defined as an increase in muscle fiber area, muscle thickness, anatomical crosssectional area or volume in this article), although four studies failed to find muscle hypertrophy 45,52,54,55) and two studies did not show the data on muscle size 56,57) . Two studies observed a decrease in fascicle length of the gastrocnemius with 58) and without 59) muscle hypertrophy, and Timmins et al 55) showed a decrease in the fascicle length of BF without muscle hypertrophy.…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 81%
“…They demonstrated that only high muscle lengthening velocity training induced an increase in VL fascicle length. However, other research groups indicated an increase in fascicle length of VL after isometric training 54,64) , slow (30°/s) isokinetic concentriconly and eccentric-only training 46) and eccentric-only (60°/ s) training 44) . Therefore, it is difficult to conclude that eccentric training, especially at high speed, can induce a preferential increase in fascicle length.…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 87%
See 1 more Smart Citation
“…However, although muscle thickness was increased similarly between groups, fascicle length was not altered after the two training interventions [5]. Likewise, isometric training at long muscle length resulted in greater increase in concentric muscle strength whereas training at short muscle lengths induced increases only in isometric strength, which was not related to changes in muscle size [6,7]. In another study, dynamic resistance training using machines and free weights at long muscle length was superior to training at short muscle length [8].…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies aimed to investigate whether training at different muscle lengths of the knee extensors induces different muscle strength and mass adaptations [5][6][7][8]. Recently, it has been reported that 8 weeks of isometric knee extension training at long muscle length induced greater strength gains compared to training at short muscle length [5].…”
Section: Introductionmentioning
confidence: 99%